2014
DOI: 10.1186/2193-1801-3-219
|View full text |Cite
|
Sign up to set email alerts
|

Performance and sex difference in ultra-triathlon performance from Ironman to Double Deca Iron ultra-triathlon between 1978 and 2013

Abstract: It was assumed that women would be able to outperform men in ultra-marathon running. The present study investigated the sex difference in performance for all ultra-triathlon distances from the Ironman distance (i.e. 3.8 km swimming, 180 km cycling and 42 km running) in the ‘Ironman Hawaii’ to the Double Deca Iron ultra-triathlon distance (i.e. 76 km swimming, 3,600 km cycling and 840 km running) between 1978 and 2013. The changes in performance and in the sex difference in performance for the annual three fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…The length of the race distance seems to be important for the trend in sex difference in performance. In long-distance triathlon races, women could reduce the sex difference only in shorter distances (e.g., Ironman triathlon) but not in longer triathlon distances (e.g., Double Iron ultra-triathlon and longer distances), where the sex difference remained unchanged or even increased over time, especially for the longer distances (16,28,30,33).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The length of the race distance seems to be important for the trend in sex difference in performance. In long-distance triathlon races, women could reduce the sex difference only in shorter distances (e.g., Ironman triathlon) but not in longer triathlon distances (e.g., Double Iron ultra-triathlon and longer distances), where the sex difference remained unchanged or even increased over time, especially for the longer distances (16,28,30,33).…”
Section: Resultsmentioning
confidence: 99%
“…The trend in sex difference in endurance and ultra-endurance over time seems to depend on the length of the performance, the kind of the discipline, and the MWR. Generally, women reduced the gap to men over time in long-distance swimming (4,14,29), long-distance cycling (31), longdistance running (15,24), and long-distance triathlon (16,19,30).…”
Section: Resultsmentioning
confidence: 99%
“…To date, the edge of human limits in ultra-triathlon was the Double Deca Iron ultra-triathlon covering the total distance of 20 Ironman triathlon races (Lenherr et al 2012; Rüst et al 2014). However, in 2013, one ultra-triathlete completed for the first time in history the total distance of 33 Ironman distances within 33 consecutive days (http://pse33.ca/intro/).…”
Section: Introductionmentioning
confidence: 99%
“…Women therefore reduced the performance difference between sexes only in Ironman triathlons, where their participation rate was the highest among ultratriathlons. 30 Furthermore, the sex difference in performance increased with increasing length of an event, from ~11.3% in the Ironman World Championship Hawaii “Ironman Hawaii” 29 to ~30% in Deca Iron ultratriathlons. 26 …”
Section: Discussionmentioning
confidence: 98%
“… 26 Of interest are the split times in the ultratriathlon, as they can be directly compared to ultrarunning. Rüst et al 30 found a decrease in the performance difference between sexes in running split times in Ironman triathlons but not in Double, Triple, or Deca Iron ultratriathlons. Women therefore reduced the performance difference between sexes only in Ironman triathlons, where their participation rate was the highest among ultratriathlons.…”
Section: Discussionmentioning
confidence: 99%